Party Positions on Differentiated European Integration in the Nordic Countries: Growing Together, Growing Apart? - Benjamin Leruth; Jarle Trondal; Stefan Gänzle (Politics and Governance, 2020)
The Nordic countries constitute an interesting laboratory for the study of differentiated European Integration. Even though Denmark, Finland, Iceland, Norway, and Sweden share some historical, cultural, socio-economic and political characteristics, all those countries have ultimately opted for a different kind of relationship with the EU. Whereas Finland, a member of the Eurozone since its inception in 1999, has been considered to be part of the Union’s ‘inner core’ for quite some time, Iceland and Norway, in contrast, have opted to remain outside the EU albeit closely associated via the European Economic Area Agreement. The variation of relationships has also been reflected in Nordic parties’ positioning vis-à-vis European integration in general and differentiation of European integration in particular. Broadly speaking, party families can be distinguished along traditional (e.g., agrarian, Christian democratic, conservative, and social democratic) and modern (e.g., socialist left, green, and populist radical right) ideological orientations. Although political parties belonging to both the traditional and modern Nordic party families have adopted different stances on European differentiated integration, we would assume—against the backdrop of Nordic cooperation—higher levels of transnational cooperation in European matters. Consequently, this article examines the similarities and differences between parties belonging to the same ideological family, and the extent of transnational party cooperation in the Nordic countries. Drawing on a series of interviews conducted with party representatives as well as on official party documents, this article shows that although institutionalized party cooperation mostly reflects divisions between party families, such institutionalization does not include a common vision for European integration. We conclude that the low level of partisan Nordic integration is primarily caused by domestic-level factors, such as intra-party divisions, government participation and public opinion.